2010
DOI: 10.1002/adsc.200900539
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Heterogeneous Dual Catalyst Systems for Alkane Metathesis

Abstract: A fully heterogeneous and highly efficient dual catalyst system for alkane metathesis (AM) has been developed. The system is comprised of an alumina-supported iridium pincer catalyst for alkane dehydrogenation/olefin hydrogenation and a second heterogeneous olefin metathesis catalyst. The iridium catalysts bear basic functional groups on the aromatic backbone of the pincer ligand and are strongly adsorbed on Lewis acid sites on alumina. The heterogeneous systems exhibit higher lifetimes and productivities rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 22 publications
1
76
0
Order By: Relevance
“…[38] Recent experimental data have revealed that the primary products of the reaction are olefins and dihydrogen; thus, a mechanism invoking tantalum carbenes and a metallocyclobutane intermediate, as observed in olefin metathesis, is proposed (Scheme 2), [28] which shows the bifunctional role of the tantalum hydrides acting as both dehydrogenation and olefin metathesis catalysts. While both recent reports [39,40] and initial work on alkane metathesis [41] (also referred to as "molecular redistribution reaction of alkanes") always involved a dual catalyst system (see Figure 3 for selected examples), the systems developed by SOMC for alkane metathesis [42][43][44] originate from a single system {either [Ta(=CH-tBu)(CH 2 -tBu) 3 or W(ϵC-tBu)(CH 2 -tBu) 3 ]}, each grafted on the appropriate inorganic oxide. The alumina-supported tungsten system is particularly noteworthy, as it achieves high activities in alkane metathesis.…”
Section: Reactivity Of Silica-supported Tantalum Hydrides With C-h Anmentioning
confidence: 94%
“…[38] Recent experimental data have revealed that the primary products of the reaction are olefins and dihydrogen; thus, a mechanism invoking tantalum carbenes and a metallocyclobutane intermediate, as observed in olefin metathesis, is proposed (Scheme 2), [28] which shows the bifunctional role of the tantalum hydrides acting as both dehydrogenation and olefin metathesis catalysts. While both recent reports [39,40] and initial work on alkane metathesis [41] (also referred to as "molecular redistribution reaction of alkanes") always involved a dual catalyst system (see Figure 3 for selected examples), the systems developed by SOMC for alkane metathesis [42][43][44] originate from a single system {either [Ta(=CH-tBu)(CH 2 -tBu) 3 or W(ϵC-tBu)(CH 2 -tBu) 3 ]}, each grafted on the appropriate inorganic oxide. The alumina-supported tungsten system is particularly noteworthy, as it achieves high activities in alkane metathesis.…”
Section: Reactivity Of Silica-supported Tantalum Hydrides With C-h Anmentioning
confidence: 94%
“…Based on results by Brookhart and Goldman in which p-substituted tBu4 PCP complexes, including ( p-Me 2 N-tBu4 PCP)Ir [55,103] were anchored to solid supports such as γ-alumina, the Brookhart group synthesized 65d with a dimethylamino group on the triptycene backbone. Catalysts 65a and 65d (1 mM) gave comparable activities (2,800 and 2,040 TON, respectively, after 20 h) for solution-phase COA (3.9 M)/TBE (3.9 M) transfer dehydrogenation at 200 C. Attempting to anchor 65d on basic γ-alumina and acidic γ-alumina, however, resulted in catalyst decomposition yielding only 185 and 70 TON, respectively, for the same transfer dehydrogenation (also at 200 C).…”
Section: ð7þ ð8þmentioning
confidence: 99%
“…In general, olefin metathesis catalysts based on tungsten were better than those based on molybdenum, and in particular, W(NAr)(CHR)(OSiPh 3 ) 2 (73) (Ar¼2,6 diisopropylphenyl) was the most effective co-catalyst. Brookhart and coworkers have used pincer-iridium complexes with polar anchoring group supported on Al 2 O 3 in tandem with Re 2 O 7 /Al 2 O 3 to obtain remarkably high TONs in alkane metathesis [103].…”
Section: Alkane Metathesismentioning
confidence: 99%
“…[5] One approach involved attaching a basic functional group (e.g., dimethylamino) in the para-position of the phenyl ring in a "PCP pincer" ligand in order to link the Ir complex to acidic surface sites on calcined g-alumina through a Lewis acid/base interaction. In the process of evaluating Ir catalysts supported on alumina it was noted that functional alkane metathesis catalysts could be prepared simply through addition of MoA C H T U N G T R E N N U N G (NAr)A C H T U N G T R E N N U N G (CHCMe 2 Ph)A C H T U N G T R E N N U N G [OCMeA C H T U N G T R E N N U N G (CF 3 ) 2 ] 2 to the alumina-supported Ir complex and that both the Ir and the Mo catalysts appeared to be adsorbed completely onto g-alumina to give active species that function in tandem to metathesize alkanes.…”
Section: Introductionmentioning
confidence: 99%